PERLINDUNGAN HUKUM BAGI DEBITUR BANK DALAM PERJANJIAN KREDIT PEMILIKAN RUMAH (KPR): Legal Protection for Bank Debtors in Home Ownership Loan Agreements (KPR) - Wulandari, Nina (Fakultas Hukum, Universitas Trisakti, 2024)
Human beings need a home as their basic necessity. Purchasing a house through installments has been the most popular method for several decades. The Home Ownership Loan Agreement (KPR) is a legal document between the debtor and the bank regarding the purchase of a house that is paid in installments by the debtor. According to Banking Law, KPR agreements tend to have provisions that benefit the bank, including high interest rates and significant additional costs. These implications further strengthen the need for increased transparency and legal protection for debtor customers, as well as stricter regulations in the banking industry to ensure a balance of interests between the bank and the debtor, given the debtor's relatively weak position. With legal protection for debtor customers, if debtor customers incur losses or risks in the KPR agreement, the creditor is obliged to handle, address, and resolve various complaints or losses experienced by the debtor party.